2011
DOI: 10.1007/s00436-011-2734-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Trichophyton ajelloi and Lagenidium giganteum metabolites against mosquitoes after flash chromatography

Abstract: Entomopathogens are significant natural enemies for mosquitoes. We have investigated the adulticidal efficacies of metabolites of Trichophyton ajelloi and Lagenidium giganteum against Culex quinquefasciatus and Aedes aegypti simultaneously. The T. ajelloi was grown on Sabouraud's dextrose broth medium at 25 ± 2°C and relative humidity at 75 ± 5% for 15 days. L. giganteum was grown in peptone yeast extract glucose broth at 25 ± 2°C and relative humidity 75 ± 5% for 15 days. The filtrations of metabolites have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…26,27) Our results are similar to those of other studies that showed the toxicity of fungal metabolites against mosquitoes. 2,28,29) A. clavatus metabolites were found to be toxic toward adults and larvae with significant mortality rates after 72 hr. Regarding the application approach, metabolites could act by contact with adults and also by ingestion by larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27) Our results are similar to those of other studies that showed the toxicity of fungal metabolites against mosquitoes. 2,28,29) A. clavatus metabolites were found to be toxic toward adults and larvae with significant mortality rates after 72 hr. Regarding the application approach, metabolites could act by contact with adults and also by ingestion by larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Conidia are classically applied, but toxic metabolites have also been produced in liquid medium and used against mosquitoes. 1,2) Metarhizium anisopliae and Beauveria bassiana are promising alternatives to conventional insecticides for eliminating mosquito vectors. 3,4) Recently, many Aspergillus species have commonly been used against mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve species of entomopathogenic Oomycota are known to exist within six genera: Lagenidium (L. giganteum), Leptolegnia (L. caudata and L, chapmanii), Pythium (P. carolinianum, P. sierrensis, and P. flevoense), Crypticola (C. clavulifera and C. entomophaga), Couchia (C. amphora, C. linnophila, and C. circumplexa), and Aphanomyces (A. laevis) (Araújo and Hughes 2016;Mendoza et al 2018). Most are facultative parasites of mosquito larvae belonging to the genera Anopheles, Culex, Aedes, Ochlerotatus, Culiseta, Orthopodomyia, Uranotaenia, Psorophora, and Mansonia (Frances et al 1989;Woodring et al 1995;Scholte et al 2004;Patwardhan et al 2005;Vyas et al 2007;Singh and Prakash 2012;Vilela et al 2018;Shen et al 2019;Vilela et al 2019;Shen et al 2020a). Some examples of infected insects are listed in Table 1.…”
Section: Oomycotamentioning
confidence: 99%